Regenerating heavily biofouled dissolved oxygen sensors using bacterial viruses. Issue 14 (23rd February 2021) - Bayat, Fereshteh; Maddiboina, Dhanyasri; Didar, Tohid F.; Hosseinidoust, Zeinab
Abstract : Lytic bacteriophages can be utilized as a non-invasive method for removing bacterial biofilms formed on the surface of gas permeable membranes of dissolved oxygen sensors. Abstract : Bacterial biofilms are aggregates of bacterial cells embedded in a self-produced extracellular polymeric matrix. Biofilm formation has always been considered a major challenge for sensors used in underwater measurements, and is a primary source of measurement error, especially when it comes to long-term in situ monitoring. We demonstrate the utility of lytic bacteriophages (bacterial viruses) as a non-invasive strategy for removing bacterial biofilms formed on the gas permeable membrane of electrochemical dissolved oxygen sensors. Our results show that a 4 day Pseudomonas aeruginosa biofilm with a fully developed matrix significantly affected the sensor signal and response time, decreasing the signal by 32% and increasing the response time by 94%. In addition, measurements with the biofouled membrane had a very low signal to nose ratio compared to a clean sensor membrane. A single dose of overnight phage treatment effectively removed the biofilm (as indicated by scanning electron micrographs and fluorescence images of the membrane), without the need for repeated treatments. Furthermore, the sensor signal that had plummeted by 32% for a fully biofouled membrane, was returned to the original value (7.96 ± 0.27 mg L −1 ) after phage treatment and the signal to noise ratio (calculated as the ratio of mean to standard deviation) increased 8 folds for a phage-treated membrane compared to a biofouled membrane. Our data indicate near complete regeneration and signal recovery for the dissolved oxygen sensor, making the biofouled sensor reusable without the use of harsh chemicals that could destroy the fragile sensor membrane.